RicetissueTFDB: A Genome-Wide Identification of Tissue-Specific Transcription Factors in Rice - Weiying Chen; Zhenyong Chen; Fuyan Luo; Mingli Liao; Shuhong Wei; Zaijun Yang; Jun Yang (The Plant Genome, 2019)
Transcription factors (TFs) regulate plant gene expression in different tissues. To investigate TF genes in rice ( L.), a genome-wide TF identification was conducted with the japonica rice genome. This study identified 3078 putative TFs in 59 families. The TF number of the top 10 TF families accounted for 58% of the 3078 rice TFs. The three largest TF families were the myeloblastosis (MYB) superfamily, basic helix–loop–helix (bHLH), and far-red-impaired response (FAR1), which contained 413, 228, and 210 TF members, respectively. The expression profiles of the 3078 TF genes were surveyed with the RNA sequencing (RNA-seq) data of 13 rice tissue types. Based on these expression profiles, we validated 1087 TFs expressed in 13 rice tissue types, which accounted for 35.32% of the 3078 putative TFs. We further analyzed the tissue-specific TFs in rice. In total, 28, 14, 14, 10, 9, 5, 5, 4, 3, 3, 2, 11, and 1 tissue-specific TF sequences were identified in the dry seed, pistil, spikelet, aleurone, anther, ovules, embryo 25 d after pollination (DAP), seed 5 DAP, root, leaf, seed 10 DAP, shoot, and endosperm 25 DAP, respectively. Moreover, we constructed RicetissueTFDB (), a comprehensive and public rice TF database that integrates tissue expression characters, genomic location, and Gene Ontology (GO) terms for each TF. The RicetissueTFDB database will facilitate the identification of target TFs and the functional studies about rice TFs.